Literature Review: The Effect of the Covid-19 Pandemic on Fatigue and Stress Levels in Nurses in Indonesia - Eunike Merlinda Kawung; Bagoes Widjanarko; Yuliani Setyaningsih (Jurnal Ilmu Keperawatan dan Kebidanan, 2021)
Background: Along with the increasing number of confirmed cases of COVID-19, it becomes a big problem for medical staff in particular nurses as thefrontlinein dealing with COVID-19 patients, this makes nurses more likely to be exposed to infection because they directly care for patients plus work hours are longer than usual In addition to risk factors for infection, inadequate protection such as personal protective equipment (PPE) ) lacking and not conforming to standards, relatively more work, discrimination, frustration, isolation resulting in reduced contact with family and fatigue Method: The method used in this study is a scoping review by focusing on specific studies of various scopes found to be combined and dance k concise conclusions. This study uses a sample of research journals in the Sinta database from the Ministry of Research and Technology. Results: The results of the scoping review on the risk factors for work fatigue and work stress in nurses prove that there is a relationship significant between workload and shifts work of nurses on stress and fatigue levels. work of nurses